STUDI BEHAVIOR SETTINGFITUR AIR DAN SEKITARNYA (Studi kasus Dunia Fantasi, Gelanggang Samudera Jaya Ancol dan Danau Ancol, Jakarta Timur) - Trista Fristovana; Aris Munandar (Jurnal Lanskap Indonesia, 2011)
One of the elements in this environment is water.  Dufan (Dunia Fantasi), Ancol Lake and Gelanggang Samudera (GSA) are some of recreation object having water features in a different settings such as water fall, fountain, and wading that interesting to study. Such of this water feature were taken for the research. In this research water features were grouped as static to dynamic water i.e. fountain I and II in Dufan, water fall I in Dufan, static water I in Dufan, wading I and II in Ancol Lake, and water fall II and static water II in GSA.The aims of this research was to study the effect of different setting in inducing number visitor, the type of activities, various of  age and long of visit duration, visit frequency, and to identify the attributes of visitor. The result showed that the largest visitor and activities were in dynamic water feature setting. This water feature setting visitor induced by adult people. The largest visit was on the fountain feature setting II and wading I which have high shade leveland more complete site furniture and then others. The largest visit frequency was on water feature setting which have easy access in all direction. The attributes that  influence from the highest were use and significance attributes, visibility attributes  and the last on the formal setting attributes.